It’s Not Easy Being Green: A Narrative Review on the Microbiology, Virulence and Therapeutic Prospects of Multidrug-Resistant Pseudomonas aeruginosa - Payam Behzadi; Zoltán Baráth; Márió Gajdács (Antibiotics, 2021)
Pseudomonas aeruginosa is the most frequent cause of infection among non-fermenting Gram-negative bacteria, predominantly affecting immunocompromised patients, but its pathogenic role should not be disregarded in immunocompetent patients. These pathogens present a concerning therapeutic challenge to clinicians, both in community and in hospital settings, due to their increasing prevalence of resistance, and this may lead to prolonged therapy, sequelae, and excess mortality in the affected patient population. The resistance mechanisms of P. aeruginosa may be classified into intrinsic and acquired resistance mechanisms. These mechanisms lead to occurrence of resistant strains against important antibiotics—relevant in the treatment of P. aeruginosa infections—such as β-lactams, quinolones, aminoglycosides, and colistin. The occurrence of a specific resistotype of P. aeruginosa, namely the emergence of carbapenem-resistant but cephalosporin-susceptible (Car-R/Ceph-S) strains, has received substantial attention from clinical microbiologists and infection control specialists; nevertheless, the available literature on this topic is still scarce. The aim of this present review paper is to provide a concise summary on the adaptability, virulence, and antibiotic resistance of P. aeruginosa to a readership of basic scientists and clinicians.